2019
DOI: 10.1186/s13049-018-0582-2
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating stab injuries in Iceland: a whole-nation study on incidence and outcome in patients hospitalized for penetrating stab injuries

Abstract: BackgroundStudies on penetrating injuries in Europe are scarce and often represent data from single institutions. The aim of this study was to describe the incidence and demographic features of patients hospitalized for stab injury in a whole nation.Materials and methodsThis was a retrospective nationwide population-based study on all consecutive adult patients who were hospitalized in Iceland following knife and machete-related injuries, 2000–2015. Age-standardized incidence was calculated and Injury Severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
5
9
0
3
Order By: Relevance
“…The mean age of men in this cohort was 34.9 years (93.8% men); in a recent study of 547 blunt chest trauma patients the mean age was 46.6 years (74.0% men) (18). Predominance of young men is in concurrence with previous studies on penetrating trauma (4,19,20).…”
Section: Discussionsupporting
confidence: 90%
“…The mean age of men in this cohort was 34.9 years (93.8% men); in a recent study of 547 blunt chest trauma patients the mean age was 46.6 years (74.0% men) (18). Predominance of young men is in concurrence with previous studies on penetrating trauma (4,19,20).…”
Section: Discussionsupporting
confidence: 90%
“…However, higher figures were reported in South Africa and Australia compared to the present study. [14,15] In Iceland, stab injuries are reportedly uncommon with an average of four cases per year. [16] The present study revealed a male predominance (88%) with a male to female ratio of 7.5:1.…”
Section: Discussionmentioning
confidence: 99%
“…Also, stabbing was found to be the most common cause of penetrating abdominal trauma than gunshot wounds (66.67% versus 33.33%) in a previous Egyptian study (Saleem et al, 2016) but the percentage of firearm was higher as this study was conducted in upper Egypt where firearm weapons were more available. Moreover, chest and abdomen were reported as the most common sites of stab wounds (Johannesdottir et al, 2019;Nishimura et al, 2017). However, gunshot was the most common cause of penetrating injuries in other studies (Lone et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating wound is applied to wound which passes through the tissues, enters a body cavity, like abdominal cavity or thoracic cavity (Begum et al, 2014). Penetrating trauma from either gunshot wounds or stab injuries is a major healthcare problem (Johannesdottir et al, 2019). The severity of the injury varies widely depending on the site of body involved, the characteristics of the penetrating object, and the amount of energy transmitted to the tissues (Patel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%